Personalized 3D Printed Eye Gear for Microscopic Surgeons Amidst and beyond COVID-19 - Ramandeep Singh; Rajdeep Singh; Ashish Suri (Bioengineering, 2023)
The COVID-19 pandemic underscored the need for enhanced protective measures for healthcare workers, particularly surgeons, who face a heightened risk of exposure to infectious aerosols. However, conventional eye protection equipment such as face shields, goggles, or glasses often leads to ergonomic discomfort and a reduced field of view (FOV), impeding surgeons’ ability to perform microsurgical procedures with precision and ease. To address these limitations, this study aimed to develop personalized 3D-printed eye gear for microscopic surgeons based on facial anthropometry data. 3D scanning was employed to obtain facial data from ten neurosurgery residents. Utilizing computer-aided designing, eye gears tailored to the unique facial features of each participant were developed. Finite element analysis-based contact simulation was used to assess the pressure exerted by the eye gear. Multi-material 3D printing was employed to fabricate the personalized eye gear. Participants, while donning the eye gear, engaged in simulation-based micro suturing tasks at various magnifications of the operating microscope, and marked the FOV range. They provided feedback scores (1–10) on the effectiveness of the eye gear through a Likert scale questionnaire (Q1-Q8). Finite element analysis demonstrated uniform strain distribution on the face, indicating that the edges of the customized eye gear fit exactly to the user’s face. The average scores for the questionnaire Q1 to Q8 ranged from 6.8 to 8.5, with an overall mean score of 7.6. This indicates that the developed eye gear was simple to use and did not cause any discomfort. Additionally, the average reduction in the FOV was only 10.93% across the different operating microscope magnifications. These findings highlight eye gear’s potential to alleviate discomfort and enhance precision in microscopic surgeries. Consequently, personalized 3D-printed eye gear offers a promising solution for providing surgeons with a safe environment while preserving the benefits of the operating microscope.